Jennifer O'Connor-Madsen, Laura Watson and Ita Beausang (Eds.), Women and Music in Ireland, Irish Musical Studies, 13 (Woodbridge: Boydell Press, 2022), ISBN: 9781783277551, 270pp, £80 (hardcover). (Journal of the Society for Musicology in Ireland, 2026)
A Review of Jennifer O'Connor-Madsen, Laura Watson and Ita Beausang (Eds.), Women and Music in Ireland, Irish Musical Studies, 13 (Woodbridge: Boydell Press, 2022), ISBN: 9781783277551, 270pp, £80 (hardcover).